2017
DOI: 10.1016/j.ejim.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and cardiovascular prevention: Is healthy urban living a possible reality or utopia?

Abstract: Favoring correct lifestyles is the most important measure to contrast cardiovascular diseases and the epidemic of high cardiovascular risk conditions, such as obesity, diabetes, and hypertension. Lifestyle is a broad expression that includes diet, physical exercise, and psychological and socio-economic factors, each of which must be taken into due consideration because of their intertwining influences, which may be a barrier to healthy changes at both the individual and population levels. While physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…In particular, our cohort had limited differences with respect to those reported for the general population consisting of higher prevalence of female gender (+9%), married status (+15%) and education level (>9 years: +14%). However, we are confident that these factors may have hardly influenced the high prevalence of NAFLD observed in our cohort since they are rather well known protective metabolic and cardiovascular factors . Furthermore, this is a single centre study and our results may potentially have limited validity in different populations and settings.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In particular, our cohort had limited differences with respect to those reported for the general population consisting of higher prevalence of female gender (+9%), married status (+15%) and education level (>9 years: +14%). However, we are confident that these factors may have hardly influenced the high prevalence of NAFLD observed in our cohort since they are rather well known protective metabolic and cardiovascular factors . Furthermore, this is a single centre study and our results may potentially have limited validity in different populations and settings.…”
Section: Discussionmentioning
confidence: 79%
“…A recent meta-analysis reported a prevalence of NAFLD of 23.7% in Europe, with rates ranging from in obesity prevalence, the main risk factor for NAFLD, especially in the southern part of Italy. 29 Studies conducted in northern European countries in the last few years have confirmed an increasing prevalence of NAFLD, ranging from 34% to 41%. 30,31 However, we cannot rule out that differences in methods used for diagnosing steatosis, or in CAP thresholds, could also contribute to explaining the observed differences.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Parallel to progressive urbanization, the prevalence of overweight/obesity is continuously rising 1 even among children and adolescents. 2 Therefore, obesity represents a real emergency in the Western world due to its association with many health problems among which reduced life expectancy, 3 compromised quality of life, 4 increased metabolic complications such as diabetes and cardiovascular (CV) morbidity and mortality. 5 The global burden of obesity is also associated with high costs and represents a serious threat to the sustainability of health systems.…”
Section: Introductionmentioning
confidence: 99%